Perspectives on developing a diverse, knowledgeable and inclusive scientific community in the shifting landscape of US scientific ocean drilling - Brittany N. Hupp; Mohammed S. Hashim; Raquel Bryant; Christopher W. Kinsley; Alexandra Villa; Lucien Nana Yobo; John O. Ajayi (Earth Science, Systems and Society)
Scientific ocean drilling (SciOD) has been invaluable in advancing our understanding of Earth history. However, the most recent international SciOD programme ended in 2024, alongside the non-renewal of the riserless drilling vessel, the JOIDES Resolution. The US has not committed to joining a new SciOD programme despite prior efforts focused on important scientific priorities (e.g. climate change, assessing natural hazards). During this critical juncture, we argue that incorporating accessibility, justice, equity, diversity and inclusion (AJEDI) efforts will further develop a cohesive community that is well prepared to tackle questions critical to the US and global community. Herein we provide recommendations to develop a knowledgeable and diverse community of scientists in the changing landscape of US SciOD, as informed by historical participation data and recent efforts by early career scientists. Recommendations focus on accessible training opportunities, enhanced stewardship of archived materials, additional funding for research at all academic levels, inclusion of cultural advisors and social scientists, and a commitment to continuing SciOD education. By pursuing these recommendations, the US SciOD community could become a leader for modelling AJEDI principles and ensuring equitable knowledge transfer that is needed to reimagine and rebuild a new, inclusive SciOD programme.